Investasi Digital Sebagai Solusi Mengurangi Perilaku Konsumtif Milenial Masa Pandemi Covid-19 - Ahmad Rosyid Nur Ismail; Kurnia Noviartati; Syahril Syahril; Achmad Rizalul Fikri (UNIVERSITAS PGRI MADIUN, 2021)
This research aims to identify changes in people's consumptive behavior, especially the millennial generation during the Covid-19 pandemic and digital investment as a solution to reduce consumptive behavior. This research is qualitative research using a narrative review writing technique. The data collection technique used in this research is documentation from secondary data sources. Researchers download secondary data from the internet in the form of journals, research articles, government agency reports, survey results, and books. The collected data were then analyzed using an interactive analysis model with the stages of analysis including data collection, data reduction, data presentation, drawing conclusions, or data verification. The results of this study indicate that changes in consumptive behavior in the Covid-19 pandemic can be seen based on four things, namely: consumptive purposes, differences in factors that affect consumptive behavior, media, and transaction tools. Meanwhile, solutions to reduce consumptive behavior based on factors owned by investment and consumptive behavior create millennials.